Configurable Integration of On‐Chip Quantum Dot Lasers and Subwavelength Plasmonic Waveguides. Issue 21 (6th April 2018) - Rong, Kexiu; Gan, Fengyuan; Shi, Kebin; Chu, Saisai; Chen, Jianjun
Abstract: The integration of on‐chip dielectric lasers and subwavelength plasmonic waveguides has attracted enormous attention because of the combination of both the advantages of the high performances of the small dielectric lasers and the subwavelength plasmonic waveguides. However, the configurable integration is still a challenge owing to the complexity of the hybrid structures and the damageability of the gain media in the multistep micro/nanofabrications. By employing the dark‐field optical imaging technique with a position uncertainty of about 21 nm and combining the high‐resolution electron beam lithography, the small colloidal quantum dot (CQD) lasers without any damages are accurately aligned with the silver nanowires. As a result, the integration of the CQD lasers and the silver nanowires can be flexibly configured on chips. In the experiment, the tangential coupling, radial coupling, and complex coupling between the high‐performance CQD lasers and the subwavelength silver nanowires are demonstrated. Because of the subwavelength field confinements of the silver nanowires, the deep‐subwavelength coherent sources (multimode, one‐color single‐mode, or two‐color single‐mode) with a mode area of only 0.008λ 2 are output from these hybrid structures. This configurable on‐chip integration with high flexibility and controllability will greatly facilitate the developments of the complex functional hybrid photonic–plasmonic circuits. Abstract : By employing the dark‐field optical imaging technique with a position uncertainty of about 21 nm, the integration of small colloidal quantum dot lasers and subwavelength plasmonic waveguides is flexibly configured on chips based on electron‐beam lithography. Deep‐subwavelength coherent sources (multimode, one‐color single‐mode, and two‐color single‐mode) with a mode area of 0.008λ 2 are output from the hybrid structures.